2015
DOI: 10.1111/aor.12417
|View full text |Cite
|
Sign up to set email alerts
|

A New Asymmetric Directional Microphone Algorithm With Automatic Mode‐Switching Ability for Binaural Hearing Support Devices

Abstract: For hearing support devices, it is important to minimize the negative effect of ambient noises for speech recognition but also, at the same time, supply natural ambient sounds to the hearing-impaired person. However, conventional fixed bilateral asymmetric directional microphone (DM) algorithms cannot perform in such a way when the DM-mode device and a dominant noise (DN) source are placed on the same lateral hemisphere. In this study, a new binaural asymmetric DM algorithm that can overcome the defects of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Under real-world conditions, some individuals have hearing impairment with symmetric left/right smearing, whereas others have hearing impairment with asymmetric left/right smearing (Kim et al 2015). Therefore, in the main experiments, we performed two separate experiments.…”
Section: Protocols Of the Subjective Testsmentioning
confidence: 99%
“…Under real-world conditions, some individuals have hearing impairment with symmetric left/right smearing, whereas others have hearing impairment with asymmetric left/right smearing (Kim et al 2015). Therefore, in the main experiments, we performed two separate experiments.…”
Section: Protocols Of the Subjective Testsmentioning
confidence: 99%
“…A maximum flow velocity of 0.94 m/s was observed at the region downstream of the percutaneous valve at the superior vena cava (SVC). Maximum RSS value of 2076.1 dynes/cm was observed downstream of the valve at the inferior vena cava during the deceleration phase while maximum TKE measured was 572.6 J/m at the upstream of the valve in the SVC during the peak flow phase. While these values appear high, they are significantly lower than those reported in prosthetic mitral and aortic valves.…”
Section: Valves and Vascularmentioning
confidence: 90%
“…Jinryoul Kim et al of Hanyang University, Seoul, Korea reported on an asymmetric directional microphone (DM) algorithm with automatic mode‐switching ability for binaural hearing support devices. The new algorithm can estimate the position of a specific dominant noise (DN) in the 90°‐270° range and switch directional‐ and omnidirectional‐mode devices automatically if the DM‐mode device and the DN are placed in opposite lateral hemispheres.…”
Section: Auditory Supportmentioning
confidence: 99%